CD82 attenuates TGF-β1-mediated epithelial-mesenchymal transition by blocking smad-dependent signaling in ARPE-19 cells - Lee, Hyesook; Han, Jung-Hwa; Kang, Yun Jeong; Hwangbo, Hyun; Yoon, Aeseon; Kim, Hyung-Sik; Lee, Dongjun; Lee, Soo Yong; Choi, Byung Hyun; Kim, Jae-Joon; Kim, Seo Rin; Choi, Yung Hyun; et al. (Frontiers in Pharmacology, 2022)
In retinal pigment epithelial (RPE) cells, transforming growth factor-beta (TGF-β) plays a critical role in epithelial-mesenchymal transition (EMT), which contributes to various fibrotic retinal disorders. In the present study, we investigated the effect of recombinant human cluster of differentiation 82 (rhCD82), a tumor metastasis suppressor, on TGF-β-induced EMT in the human RPE cell line APRE-19. The results show that TGF-β1 significantly enhanced cell migration, invasion and the expression of EMT-mediate factors in ARPE-19 cells. However, rhCD82 markedly inhibited cell mobility and the expression of epithelial marker, zonula occludens-1, as well as increased the expression of mesenchymal markers, such as vimentin and α-smooth muscle actin in TGF-β1-treated APRE-19 cells. In addition, TGF-β1 upregulated the phosphorylation of Smad, extracellular signal regulated kinase (ERK) and glycogen synthase kinase-3β (GSK-3β), but only phosphorylation of Smad was suppressed by rhCD82. Noteworthy, rhCD82 greatly suppressed the expression of TGF-β receptor I (TGFRI), TGFRII and integrins in TGF-β1-treated APRE-19 cells. In particular, the result of molecular docking analysis and structural modeling show that rhCD82 partially interacts with the TGF-β1 binding sites of TGFRI, TGFRII, integrin β1 and integrin αv. Taken together, this finding suggested that rhCD82 suppressed TGF-β1-induced EMT of RPE by blocking of Smad-dependent pathway, which is caused by rhCD82 interaction with TGFRs and integrins, suggesting new insight into CD82 as a potential therapeutic strategy in fibrotic retinal disorders.